Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1088/1361-6501/ac8891
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent fault warning method of rotating machinery with intraclass and interclass infographic embedding

Abstract: Rotating machinery is widely used in industrial production facilities, and once a failure occurs, it can be catastrophic. Alerting to potential defects in time to prevent further equipment degradation is a challenging task. In this paper, a novel two-stage fault warning framework is proposed for early fault warning of rotating machinery. Specifically, a new method based on intra-class and inter-class neighborhood information graph embedding orthogonal discriminant projection (IINGEODP) is firstly adopted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Zhao and Zhang took the time-frequency image of the original signal as the input of the encoder and used parallel adversarial learning inference to train the encoder and decoder independently at the same time, so that the extracted features are similar to well-classified samples and the original signal is reconstructed [11]. Sun et al [19] conducted unsupervised training of a model based on the criterion of compressing homogeneous distance and distancing heterogeneous distance. Based on intra-class and inter-class neighborhood information graphs embedding orthogonal discriminant projection, the global distribution feature information and local geometric structure information of the data were extracted.…”
Section: Unsupervised Trainingmentioning
confidence: 99%
“…Zhao and Zhang took the time-frequency image of the original signal as the input of the encoder and used parallel adversarial learning inference to train the encoder and decoder independently at the same time, so that the extracted features are similar to well-classified samples and the original signal is reconstructed [11]. Sun et al [19] conducted unsupervised training of a model based on the criterion of compressing homogeneous distance and distancing heterogeneous distance. Based on intra-class and inter-class neighborhood information graphs embedding orthogonal discriminant projection, the global distribution feature information and local geometric structure information of the data were extracted.…”
Section: Unsupervised Trainingmentioning
confidence: 99%
“…Furthermore, adding an interpretability module, like the attention mechanism, has proven to be a highly effective way to improve the interpretability and accuracy of LSTM-based models in RUL prediction [12,13]. Some researchers have demonstrated that integrating attention with LSTM improves accuracy and interpretability, while also highlighting significant degradation aspects, which is crucial for improving RUL prediction performance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Condition assessment includes evaluating mechanical operation, detecting anomalies, tracking degradation, and determining the degree of rotating machinery [9]. Faults in rotating machinery often start subtly and progress gradually over time [10]. Major accidents may occur if abnormalities are not detected in time.…”
Section: Introductionmentioning
confidence: 99%